Ecology and taxanomy of potential amnesic shellfish poising (ASP) causing diatom Pseudo-nitzschia species (bacillariophyceae) in Malaysian water - Su, Suriyanti Nyun Pau. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Amnesic shellfish poisoning (ASP) is a type of human intoxication due to consumption of contaminated shellfish with algal origin domoic acid (DA). In this study, seasonal occurrence of Pseudo-nitzschia species in two estuarine waters was investigated by plankton and water samplings for 30 months period at fortnightly interval. The abundance of Pseudo-nitzschia was apparently influenced by water salinity, pH, silicate concentrations and precipitation rates. Pseudo-nitzschia occured mainly between April and September but cells were mostly abundant in May. Highest cell density recorded in Santubong and Samariang was 8.0x103 cells L-1 and and 2.9x104 cells L-1 respectively. Based on ultrastructural features of Pseudo-nitzschia under transmission and scanning electron microscopic (TEM and SEM) observations, the Pseudo-nitzschia species were identified as Pseudo-nitzschia pungens and P.brasiliana